An alternative allosteric regulation mechanism of an acidophilic l‐lactate dehydrogenase from Enterococcus mundtii 15‐1A. Issue 1 (6th September 2014) - Matoba, Yasuyuki; Miyasako, Masashi; Matsuo, Koichi; Oda, Kosuke; Noda, Masafumi; Higashikawa, Fumiko; Kumagai, Takanori; Sugiyama, Masanori
Abstract : A plant‐derived Enterococcus mundtii 15‐1A, that has been previously isolated from Brassica rapa L. subsp. nipposinica (L.H. Bailey) Hanelt var. linearifolia by our group, possesses two kinds ofl ‐lactate dehydrogenase (l ‐LDH): LDH‐1 and LDH‐2. LDH‐1 was activated under low concentration of fluctose‐1, 6‐bisphosphate (FBP) at both pH 5.5 and 7.5. Although LDH‐2 was also activated under the low concentration of FBP at pH 5.5, a high concentration of FBP is necessary to activate it at pH 7.5. The present study shows the crystal structures of the acidophilic LDH‐2 in a complex with and without FBP and NADH. Although the tertiary structure of the ligands‐bound LDH‐2 is similar to that of the active form of other bacteriall ‐LDHs, the structure without the ligands is different from that of any other previously determinedl ‐LDHs. Major structural alterations between the two structures of LDH‐2 were observed at two regions in one subunit. At the N ‐terminal parts of the two regions, the ligands‐bound form takes an α‐helical structure, while the form without ligands displays more disordered and extended structures. A vacuum‐ultraviolet circular dichroism analysis showed that the α‐helix content of LDH‐2 in solution is approximately 30% at pH 7.5, which is close to that in the crystal structure of the form without ligands. A D241N mutant of LDH‐2, which was created by us to easily form an α‐helix at one of the two parts, exhibited catalytic activity even in the absence of FBP at both pH 5.5 and 7.5. Abstract : Enterococcus mundtii 15‐1A harbors two kinds ofl ‐lactate dehydrogenase (l ‐LDH). One of thel ‐LDHs, named LDH‐2, displays a maximal catalytic activity at pH 5.5. To activate LDH‐2 at pH 7.5, a high concentration of FBP is necessary. LDH‐2 takes a compact inactive form distinctive from that of other bacteriall ‐LDHs. Difficulty in forming an α‐helix is related to the regulation of the LDH‐2 activity.